Utilizing renewable energy through development of green alternative lubricant / Muhammad Safwan Rosly … [et al.] - Rosly, Muhammad Safwan; Azhari, Muhamad Azwar; Khairulanuar, Muhamad Asyraaf; Zainudin, Muhammad Abi Dzar (Division of Research and Industry Linkages, 2017)
The development o f bio-lubricant which is biodegradable, non-toxic and renewable resources are desired since the existing mineral based lubricant are of non renewable resources and prone to environmental issues. W ith increasing concerns of environmental issues, palm oil has been use to replaced mineral oil as lubricant. Zinc Dialkyl Dithiophosphate (ZDDP) and Molybdenum Dialkyl Dithiophosphate (MoDTP) was introduced into palm oil to improve the tribological properties in order to make it comparable w ith commercialized mineral based lubricant. Palm oil w ith the addition of ZDPP and MoDTP has shown superior tribological properties with reduction of coefficient of friction and wear scar diameter compared to SAE 15W-40 mineral based lubricant. Addition of ZDDP at 2wt% and MoDTP at 0.05wt% into palm oil is seen as the most desirable concentration as it surpass the lubrication properties of commercialized SAE15W-40 mineral based oil.